The Mediating Role of Rumination in the Relationship Between University Students' Attachment Dimensions and Future Anxiety - İlayda Üçer; Manolya Çalışır (Clinical Journal of Health Sciences, 2026)
The purpose of this study is to examine the mediating role of ruminative thought processes in the relationship between attachment dimensions and future anxiety among college students. To this end, 420 participants were included in the study. Participants completed the Sociodemographic Information Form, the Experiences in Close Relationships Inventory II, the Rumination Response Scale, and the Future Anxiety Scale for College Students online. According to the study results, there are positive correlations between the total ruminative score and its subscales and anxious attachment. Similarly, there are positive correlations between the total ruminative score and its subscales, as well as with avoidant attachment. Furthermore, positive correlations were found between the total score and the subscales of future anxiety, and between the total score and the subscales of rumination. In addition, positive correlations were identified between the total score and subscales of future anxiety and both anxious and avoidant attachment styles. According to the results of multiple regression analysis, avoidant and anxious attachment styles, along with the level of rumination, positively predict future anxiety. The results of the mediation analysis revealed that ruminative thoughts have a partial mediating effect on the relationship between anxious attachment and future anxiety. Similarly, it was found that ruminative thoughts have a partial mediating effect on the relationship between avoidant attachment and future anxiety. Based on the research findings, incorporating structured intervention techniques aimed at increasing awareness of ruminative thinking tendencies into psychoeducational programs targeting individuals’ attachment styles may be an effective strategy for reducing future anxiety.